Relación entre microalbuminuria, urea, creatinina y ácido úrico como pruebas para valorar daño renal en pacientes del Club de hipertensos den Centro de Salud N° 4 del cantón Catamayo. - Pinto Torres, Jackeline Margoth (2014)
Hypertension affects many people and is a public health problem of enormous proportion since sufferers often suffer complications such as cardiovascular diseases, disorders of the retina, especially the nervous system and kidney; causes kidney damage and important in the progression to nephropathy factor, plus it causes 30% of chronic and terminal renal failure. The investigation is a analytic study type, descriptive cross section, it was applied to 65 patients, whose main objective is the "DETERMINATION MICROALBUMINURIA, urea, creatinine and uric acid AS EVIDENCE TO ASSESS DAMAGE RENAL PATIENTS CLUB OF HYPERTENSION HEALTH CENTER No. 4 OF CANTON CATAMAYO ", for which blood analysis is performed to determine the concentration of urea, creatinine and uric acid and determining urine microalbuminuria. The results were: After analysis of urea, creatinine and uric acid showed that 16 patients (25%) had increased values and 49 patients (75%) had normal values; microalbuminuria after analysis of 49 patients (75%) had normal and 16 patients (25%) had increased values. When you reach the end of the study concluded that a significant percentage of the population could develop some kind of kidney damage due to high blood pressure, lack of capacity to excrete metabolites such as urea, creatinine and uric acid accumulated blood level and microalbuminuria. Keywords: Arterial hypertension, Renal Hurt, Microalbuminuria, Urea, Creatinine, Uric Acid.